Early Patent Disclosure and R&D Investment in Family Firms - Katrin Hussinger; Wunnam Basit Issah (British Journal of Management, 2023)
This paper shows that the American Inventor's Protection Act, which introduced the disclosure of patent applications after 18 months, that is, before a grant decision is taken and, hence, before it is known whether the respective technology will receive legal protection, is associated with a reduction of family firms' research and development (R&D) investment. This suggests that early disclosure of patent applications is perceived as a threat to family firms' innovation activity and discourages their R&D investment. This finding deserves our attention because family firms account for a large share of the US economy, and a reduction in their R&D investment can have long-term consequences.
Keywords: 650